Urinary Nitric Oxide Levels Are Associated with Blood Pressure, Fruit and Vegetable Intake and Total Polyphenol Excretion in Adolescents from the SI! Program - Sonia L. Ramírez-Garza; Emily P. Laveriano-Santos; Camila Arancibia-Riveros; Jose C. Carrasco-Jimenez; Patricia Bodega; Amaya de Cos-Gandoy; Mercedes de Miguel; Gloria Santos-Beneit; Juan Miguel Fernández-Alvira; Rodrigo Fernández-Jiménez; Jesús Martínez-Gómez; Ramón Estruch; et al. (Antioxidants, 2022)
Nitric oxide (NO) is important to cardiovascular health (CVH), and its bioavailability could be regulated by the antioxidant effect of polyphenols, improving endothelial function and consequently blood pressure (BP). However, scant research has been carried out on NO and CVH correlates in adolescent populations. Therefore, our aim was to investigate the association between NO and the CVH status and other health factors in adolescents. NO, total polyphenol excretion (TPE), anthropometric measurements, BP, blood lipid profile, blood glucose, diet, physical activity, and smoking status were recorded, while CVH score was classified as ideal, intermediate, and poor. Negative associations were observed between NO and body mass index, body fat percentage, BP, and triglycerides; and positive associations between NO and skeletal muscle percentage, HDL-cholesterol, fruit and vegetable intake, and TPE was observed. To capture more complex interactions among different factors, multiple linear regression was performed, obtaining a significant association between NO and fruit and vegetable intake (β = 0.175), TPE (β = 0.225), and systolic BP (β = −0.235). We conclude that urinary NO levels are positively associated with the consumption of fruits and vegetables rich in antioxidants such as polyphenols and negatively associated with systolic BP.